2015
DOI: 10.1155/2015/736175
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Practice, and Associated Factors towards Prevention of Surgical Site Infection among Nurses Working in Amhara Regional State Referral Hospitals, Northwest Ethiopia

Abstract: Knowledge and practice of nurses about surgical site infections (SSIs) are not well studied in Ethiopia. This paper contains findings about Northwest Ethiopian nurses' knowledge and practice regarding the prevention of SSIs. The main objective of the study was to assess knowledge, practice, and associated factors of nurses towards the prevention of SSIs. The study was done using a questionnaire survey on randomly selected 423 nurses who were working in referral hospitals during the study period. The study show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
45
8
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 19 publications
21
45
8
2
Order By: Relevance
“…This result was congruent with [36], who reported that only 6% of three hundred and thirty three nurses who work in surgical wards and operating theatre have had additional exposure to special training courses about surgical site infection prevention where the rest of the study sample (94%) did not. Tentatively, the lack of exposure to special training courses is a challenging problem facing Jordanian nurses nowadays, which may be due to the lack of conducting well-structured special courses regarding evidence based guidelines for the pre-vention of SSIs in Jordanian public governmental hospitals despite of the availability of continuing education units in all of these hospitals, this problem may be refer to defect in continuing education programs implementation which explained by the lack of proper assessment of their nurses educational needs, and the lack of motivation from both the nurses themselves and the hospital administration.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This result was congruent with [36], who reported that only 6% of three hundred and thirty three nurses who work in surgical wards and operating theatre have had additional exposure to special training courses about surgical site infection prevention where the rest of the study sample (94%) did not. Tentatively, the lack of exposure to special training courses is a challenging problem facing Jordanian nurses nowadays, which may be due to the lack of conducting well-structured special courses regarding evidence based guidelines for the pre-vention of SSIs in Jordanian public governmental hospitals despite of the availability of continuing education units in all of these hospitals, this problem may be refer to defect in continuing education programs implementation which explained by the lack of proper assessment of their nurses educational needs, and the lack of motivation from both the nurses themselves and the hospital administration.…”
Section: Discussionsupporting
confidence: 85%
“…However, this result supported also by another research findings investigated nurses' knowledge regarding SSIs prevention which was describe the overall knowledge scores as inadequate [36], their results attributed primarily to lack of exposure to special training courses regarding to preoperative and postoperative nursing interventions in order to prevent SSI.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This result is close to the result by Eskander et al [25] which showed that the level of practice was more than 75%. However, it is less than what was obtained by Fashafsheh et al [16] as it was 91.14%, but it is higher than what was found in many other studies [18,20,26,27] as this level of practice accounted for 20, 48.7, 55.3, and 57.5%, respectively. This discrepancy in results could be due to the difference in participants' attitudes towards utilizing infection control measure methods.…”
Section: Discussioncontrasting
confidence: 62%
“…Information to policy makers to improve the working condition as a result is limited. Even though Assessment of knowledge, attitude and practice of health care workers on infection prevention in health institution done at Bahir Dar and Addis Ababa [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] to the extent of our knowledge there is no study done on health care workers in Dessie Referral Hospital, Ethiopia. Therefore, this study was aimed to assess the knowledge and practice of health care professionals towards infection prevention in Dessie Referral Hospital, North East Ethiopia.…”
Section: Significance Of the Studymentioning
confidence: 99%